Ultra-lightweight robotic hip exoskeleton with anti-phase torque symmetry for enhanced walking efficiency - Bokman Lim; Byungjune Choi; Changhyun Roh; Jewoo Lee; Yong-Jae Kim; Younbaek Lee (Scientific Reports, 2025)
Abstract This paper presents a novel robotic exoskeleton that is exceptionally lightweight and compact, while providing effective gait assistance. To maximize the system’s assistance-to-weight/size ratio, the design focuses on two key aspects of human gait mechanics: (1) the contribution of the hip joints to power generation, and (2) the symmetrical nature of hip flexion and extension torques during walking. Based on these principles, we developed a compact hip exoskeleton with a single actuator. This actuator simultaneously drives the hip joint in the sagittal plane, facilitating both flexion and extension during gait. An adaptive delayed output feedback controller was implemented, ensuring consistent performance across diverse walking conditions using a single rotational sensor and actuator. To evaluate the exoskeleton’s effectiveness, a 4-week outdoor walking exercise program was conducted with nine elderly participants. Their gait, balance, and muscle strength were measured before and after the program to assess improvements. Results showed significant improvements in walking speed (14.8% in the 10-m walk and 10.6% in the 6-min walk), as well as enhanced performance in the timed up-and-go test (24.5%) and the short physical performance battery test (18.7%). Ankle dorsiflexion and plantar flexion muscle strength increased by 75.45% and 45.8%, respectively. Additionally, metabolic measurements from three young adults indicated a 13.6 ± 3.2% reduction in the net metabolic cost of walking with the exoskeleton compared to walking without it. These results demonstrate that the single actuator-based hip exoskeleton offers effective gait assistance while maintaining a lightweight and compact design, highlighting its potential for widespread use in various applications.